USE OF ANTHROPOMETRICAL DATA OF WORKERS FOR DESIGN OF INDIVIDUAL PROTECTION EQUIPMENT - Gridiaiev, Volodymyr; Manidina, Yevheniia; Karpenko, Anna; Rusakov, Oleksandr (Scientific Journal "Metallurgy", 2024)
Long-term work of workers in harmful and difficult working conditions leads to the occurrence of occupational diseases in them. The largest share among all known occupational diseases caused by harmful and dangerous production factors is respiratory diseases. According to the regulations on labor protection and the collective agreement, the employer is obliged to provide the worker with personal protective equipment (PPE). The work examines the main designs of personal respiratory protection equipment (PPE), and identifies their main structural elements. A study of the anthropometric dimensions of the face of 300 workers of the coke chemical industry (KHV) was conducted. It was determined that the most influential parameters of the face for determining the protective capacity of ZIZOD are: length and width of the face, as well as the length of the lips. When comparing the research results with the data of the LANL and NIOSH tables, 20% of the agreement of the sizes of the faces of the investigated workers with the data of the first table, LANL, and 88% with the data of the second table, NIOSH, was found. It has been established that the improvement of the NIOSH table will make it possible to carry out high-precision tests of ZIZOD in domestic research laboratories. The use of such NIOSH tables is expected to allow selection of a PPE with a 90% degree of protection. On the basis of the ISO 16900-1:2020 standard "Respiratory protective devices – Methods of test and test equipment –Part 1: Determination of inward leakage" based on the standard dimensions of the Sheffield head mannequin used in determining the penetration coefficient of filtering half-masks, the face type of domestic workers was determined on KHV – medium/ wide type. Recommended main directions for improving the design of PPE to ensure their protective capacity at a high level: to produce several standard sizes of half-masks, to create an adjustable obturator according to the anthropometric parameters of the workers.